“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

Approximate simulation of the hysteresis friction of radial shaft seals - Bührmann, Tobias; Magyar, Balázs (Tribologie und Schmierungstechnik)

A Credibility and Strategic Behavior Approach in Hesitant Multiple Criteria Decision-Making With Application to Sustainable Transportation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; Tena, Emilio Cerda (IEEE Transactions on Fuzzy Systems)
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Control and Systems Engineering

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Introduction: English Linguistics, Learners and the Classroom - Hahn, Charlotte Anna; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

‘Authentic Englishes.nrw’ – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, S.; Fiege, Amanda Sophie; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Spring Forward, Don't Fall Back: The Effect of Daylight Saving Time on Road Safety - Bünnings, Christian; Schiele, Valentin (The Review of Economics and Statistics)
In this paper, we analyze the effect of light conditions on road accidents and estimate the long run consequences of different time regimes for road safety. Identification is based on variation in light conditions induced by differences in sunrise and sunset times across space and time. We estimate that darkness causes annual costs of more than £500 million in Great Britain. By setting daylight saving time year-round 8 percent of these costs could be saved. Thus, focusing solely on the short run costs related to the transition itself underestimates the total costs of the current time regime.

An apparatus to synthesize ceramic nanoparticles with a precisely adjusted temperature history and a significant mass output - Rasche, David B.; Tigges, Lena; Schmid, Hans-Joachim (Review of Scientific Instruments)

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Die „Logik“ der Überzeugungskraft - Krimphove, Dieter (Rechtstheorie)

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Single-photon sources: Approaching the ideal through multiplexing - Meyer-Scott, Evan; Silberhorn, Christine; Migdall, Alan (Review of Scientific Instruments)
Keywords: Instrumentation

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Special Issue: Predictive Security Technologies (Editorial) - Hälterlein, Jens; Ostermeier, Lars (European Journal for Security Research)
Keywords: General Medicine

Efing, Christian (Hrsg.): Sprache und Kommunikation in der beruflichen Bildung. Modellierung – Anforderungen – Förderung. Frankfurt am Main: Lang, 2015 (Wissen – Kompetenz – Text, 9). – ISBN 978-3-631-66096-6. 289 Seiten, € 62,95. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Fast Fuzzy Pattern Tree Learning for Classification - Senge, Robin; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Burst design and signal processing for the speed of sound measurement of fluids with the pulse-echo technique - Dubberke, Frithjof H.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Note: Ion-induced secondary electron emission from oxidized metal surfaces measured in a particle beam reactor - Marcak, Adrian; Corbella, Carles; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Review of Scientific Instruments)

Apparatus for the measurement of the speed of sound of ammonia up to high temperatures and pressures - Dubberke, Frithjof H.; Rasche, David B.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

High-resolution mass spectrometer for liquid metal ion sources - Wortmann, Martin; Ludwig, Arne; Meijer, Jan; Reuter, Dirk; Wieck, Andreas D. (Review of Scientific Instruments)

A dark-field microscope for background-free detection of resonance fluorescence from single semiconductor quantum dots operating in a set-and-forget mode - Kuhlmann, Andreas V.; Houel, Julien; Brunner, Daniel; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Review of Scientific Instruments)

Particle beam experiments for the analysis of reactive sputtering processes in metals and polymer surfaces - Corbella, Carles; Grosse-Kreul, Simon; Kreiter, Oliver; de los Arcos de Pedro, Maria Teresa; Benedikt, Jan; von Keudell, Achim (Review of Scientific Instruments)

Polarization-preserving confocal microscope for optical experiments in a dilution refrigerator with high magnetic field - Sladkov, Maksym; Bakker, M. P.; Chaubal, A. U.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Review of Scientific Instruments)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Compact cryogenic Kerr microscope for time-resolved studies of electron spin transport in microstructures - Rizo, P. J.; Pugžlys, A.; Liu, J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H.; van Loosdrecht, P. H. M. (Review of Scientific Instruments)

Time-dependent density-functional theory for extended systems - Botti, Silvana; Schindlmayr, Arno; Del Sole, Rodolfo; Reining, Lucia (Reports on Progress in Physics)
For the calculation of neutral excitations, time-dependent density functional theory (TDDFT) is an exact reformulation of the many-body time-dependent Schrödinger equation, based on knowledge of the density instead of the many-body wavefunction. The density can be determined in an efficient scheme by solving one-particle non-interacting Schrödinger equations—the Kohn–Sham equations. The complication of the problem is hidden in the—unknown—time-dependent exchange and correlation potential that appears in the Kohn–Sham equations and for which it is essential to find good approximations. Many approximations have been suggested and tested for finite systems, where even the very simple adiabatic local-density approximation (ALDA) has often proved to be successful. In the case of solids, ALDA fails to reproduce optical absorption spectra, which are instead well described by solving the Bethe–Salpeter equation of many-body perturbation theory (MBPT). On the other hand, ALDA can lead to excellent results for loss functions (at vanishing and finite momentum transfer). In view of this and thanks to recent successful developments of improved linear-response kernels derived from MBPT, TDDFT is today considered a promising alternative to MBPT for the calculation of electronic spectra, even for solids. After reviewing the fundamentals of TDDFT within linear response, we discuss different approaches and a variety of applications to extended systems.

Ab initio study of the half-metal to metal transition in strained magnetite - Friák, Martin; Schindlmayr, Arno; Scheffler, Matthias (New Journal of Physics)
Using density-functional theory, we investigate the stability of the half-metallic ground state of magnetite under different strain conditions. The effects of volume relaxation and internal degrees of freedom are fully taken into account. For hydrostatic compression, planar strain in the (001) plane and uniaxial strain along the [001] direction, we derive quantitative limits beyond which magnetite becomes metallic. As a major new result, we identify the bond length between the octahedrally coordinated iron atoms and their neighbouring oxygen atoms as the main characteristic parameter, and we show that the transition occurs if external strain reduces this interatomic distance from 2.06 Å in equilibrium to below a critical value of 1.99 Å. Based on this criterion, we also argue that planar strain due to epitaxial growth does not lead to a metallic state for magnetite films grown on (111)-oriented substrates.

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Reactor system for the study of high-temperature short-time sintering of nanoparticles - Kirchhof, Martin J.; Schmid, Hans-Joachim; Peukert, Wolfgang (Review of Scientific Instruments)
A high-temperature short residence time flow reactor system has been realized for the investigation of the gas phase sintering kinetics of nanoparticles separated from all other synthesis mechanisms, e.g., chemical reaction, nucleation, coagulation and condensation. Major components are a hot-wall tubular reactor for the production of unsintered aggregates consisting of spherical primary particles in the size range 10–80 nm and a sintering reactor for the investigation of the sintering kinetics at well-defined temperature and residence time history. Therefore, rapid heating and quenching of the particles at the beginning and at the end of the reaction zone, respectively, is maintained. Main parameters in the sintering reactor are: temperatures up to 1873 K and residence times in the range 8–1000 ms. The reactor conditions are characterized by temperature profile measurements with a newly constructed suction thermocouple probe and by computational fluid dynamics simulations of the residence time distributions. Exemplary results of the sintering of silica nanoparticles obtained by transmission electron microscopy analysis are presented.

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

A compact electron beam evaporator for carbon doping in solid source molecular beam epitaxy - Reuter, Dirk; Wieck, A. D.; Fischer, A. (Review of Scientific Instruments)

A compact electron beam evaporator for carbon doping in solid source molecular beam epitaxy - Reuter, Dirk; Wieck, A. D.; Fischer, A. (Review of Scientific Instruments)

Imaging of liquid crystals using a new scanning near-field optical microscope with microfabricated tips and shear force detection - Röder, Th.; Paelke, L.; Held, N.; Vinzelberg, S.; Kitzerow, Heinz-Siegfried (Review of Scientific Instruments)
Keywords: Instrumentation

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Imaging of liquid crystals using a new scanning near-field optical microscope with microfabricated tips and shear force detection - Röder, Th.; Paelke, L.; Held, N.; Vinzelberg, S.; Kitzerow, Heinz-Siegfried (Review of Scientific Instruments)
Keywords: Instrumentation

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)